MANAJEMEN PENGELOLAAN SAMPAH DINAS LINGKUNGAN HIDUP DAN PERTANAHAN KABUPATEN SITARO - STEVI SRIANI KAKESING; JOYCE RARES; VERY LONDA (JURNAL ADMINISTRASI PUBLIK, 2022)
This study aims to determine the waste management of the environmental and land office of Sitaro district. This research was conducted using a descriptive method with a qualitative approach with data sources in the form of interviews, observations and documentation. The results of this study reveal that the Department of Environment and Land of Sitaro Regency has shown its role in managing waste so that it can be further processed that provides benefits for the environment. In carrying out waste management, the Environment and Land Office of Sitaro Regency through planning has been going well. However, the implementation of waste transportation is still very minimal because of the lack of accommodation for transportation of waste. Regarding education to the community, Department employees must always carry out effective communication so that collaboration is maintained to provide benefits for the community.Â Â Keywords: Management, Management, Waste Management